Identification and Genetic Characterization of Ralstonia solanacearum Species Complex Isolates from Cucurbita maxima in China - She, Xiaoman; Yu, Lin; Lan, Guobing; Tang, Yafei; He, Zifu (Frontiers in Plant Science, 2017)
Ralstonia solanacearum species complex is a devastating phytopathogen with an unusually wide host range, and new host plants are continuously being discovered. In June 2016, a new bacterial wilt on Cucurbita maxima was observed in Guangdong province, China. Initially, in the adult plant stage, several leaves of each plant withered suddenly and drooped; the plant then wilted completely, and the color of their vasculature changed to dark brown, ultimately causing the entire plant to die. Creamy-whitish bacterial masses were observed to ooze from crosscut stems of these diseased plants. To develop control strategies for C. maxima bacterial wilt, the causative pathogenic isolates were identified and characterized. Twenty-four bacterial isolates were obtained from diseased C. maxima plants, and 16S rRNA gene sequencing and pathogenicity analysis results indicated that the pathogen of C. maxima bacterial wilt was Ralstonia solanacearum. The results from DNA-based analysis, host range determination and bacteriological identification confirmed that the 24 isolates belonged to R. solanacearum phylotype I, race 1, and eight of these isolates belonged to biovar 3, while 16 belonged to biovar 4. Based on the results of partial egl gene sequence analysis, the twenty-four isolates clustered into three egl- sequence type groups, sequevars 17, 45 and 56. Sequevar 56 is a new sequevar which is described for the first time in this paper. An assessment of the resistance of 21 pumpkin cultivars revealed that C. moschata cv. Xiangyu1 is resistant to strain RS378, C. moschata cv. Xiangmi is moderately resistant to strain RS378, and 19 other pumpkin cultivars, including four C. maxima cultivars and 15 C. moschata cultivars, are susceptible to strain RS378. To the best of our knowledge, this is the first report of C. maxima bacterial wilt caused by R. solanacearum race 1 in the world. Our results provide valuable information for the further development of control strategies for C. maxima wilt disease.